Rancang Bangun Antena Vivaldi Frekuensi 478-694 MHz Untuk TV Digital - Wangi Zarmen; Rizadi Sasmita Darwis (Politeknik Caltex Riau, 2021)
Nowadays, television is having a massive development, to fulfill the needs of the technology evolution which started from analog TV, it has advanced into digital TV. In this research, vivaldi antennathat was designed can work on digital TV frequency, that is at 478-694 MHz. Vivaldi antenna has several advantages, such as; simple structure, light weight, and most importanly ultra-wideband, so this antenna becomes a favorite tool in communication systems.The substrate of vivaldi antenna in this research is designed for using FR-4 with a dielectric permitivity is 4.6 mm. This antenna is designed with a type of antipodal vivaldi antenna by adding a triangular dielectric director to add the gain of antenna. The antenna is the simulated by using software simulator before being manufactured and measured. The mesuarement obtained vivaldi antenna that have been made to have a return loss of -18.86 and VSWR of 1.29 in the frequency range of 538.8-751.4 MHz, a gain of dBi, and unidirectional radiation patterns. With these characteristic results the antenna can work well at a frequency of 538.8-751.4 MHz.